2022
DOI: 10.1002/jpen.2463
|View full text |Cite
|
Sign up to set email alerts
|

GLIM‐defined malnutrition and overall survival in cancer patients: A meta‐analysis

Abstract: Background Malnutrition defined by the Global Leadership Initiative on Malnutrition (GLIM) has been associated with cancer mortality, but the effect is limited and inconsistent. We performed this meta‐analysis aiming to assess this relationship in patients with cancer. Methods We systematically searched Embase, PubMed, Web of Science, Cochrane, CINAHL, CNKI, Wanfang, and VIP databases from January 1, 2019, to July 1, 2022. Studies evaluating the prognostic effect of GLIM‐defined malnutrition on cancer survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Because each individual must still meet a phenotypic criterion (weight loss, low BMI, or reduced muscle mass) to receive a diagnosis of malnutrition, 13–15 one cannot be diagnosed with malnutrition on the basis of meeting only an etiologic criterion. In general, the GLIM approach has had similar utility in identifying malnourished individuals and in predicting adverse outcomes as other approaches, such as SGA and AAIM 34–45 …”
Section: Resultsmentioning
confidence: 99%
“…Because each individual must still meet a phenotypic criterion (weight loss, low BMI, or reduced muscle mass) to receive a diagnosis of malnutrition, 13–15 one cannot be diagnosed with malnutrition on the basis of meeting only an etiologic criterion. In general, the GLIM approach has had similar utility in identifying malnourished individuals and in predicting adverse outcomes as other approaches, such as SGA and AAIM 34–45 …”
Section: Resultsmentioning
confidence: 99%
“…26 In the present study, NIPGS incorporating shown GLIM-defined malnutrition is a reliable predictor of survival in patients with cancer. [28][29][30] Both models take into account the impact of inflammation on nutritional status and survival. However, there may be several advantages to utilizing our NIPGS over GLIM.…”
Section: Discussionmentioning
confidence: 99%
“…The NIPGS in our study consists of four grades with 16 possible combination groups that could provide a more finely tuned survival prediction. Numerous studies have shown GLIM‐defined malnutrition is a reliable predictor of survival in patients with cancer 28–30 . Both models take into account the impact of inflammation on nutritional status and survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, other methodology designed for general use in all adult patient populations has been studied in patients with cancer but has criteria that do not exactly agree with the earlier proposed staging. 5,6 Consequently, a lack of understanding regarding integration of nutrition interventions with other reported treatment modalities in managing CC is also likely to be a challenge for clinicians. These inconsistencies contribute to knowledge and practice gaps for clinicians, which frequently result in inconsistent patient care.…”
mentioning
confidence: 99%
“…For example, a system that describes various stages of adult CC has been proposed with early interventions possibly reversing stages 1 and 2, whereas refractory cachexia (stage 3) is not likely to respond to interventions. However, other methodology designed for general use in all adult patient populations has been studied in patients with cancer but has criteria that do not exactly agree with the earlier proposed staging 5,6 . Consequently, a lack of understanding regarding integration of nutrition interventions with other reported treatment modalities in managing CC is also likely to be a challenge for clinicians.…”
mentioning
confidence: 99%